CATEGORIZATION OF LANGUAGE NOMINATIONS IN THE SOCIOLINGUISTIC SPACE OF THE PEOPLE’S REPUBLIC OF CHINA - Svetlana A Moskvitcheva (RUDN Journal of Language Studies, Semiotics and Semantics, 2018)
In this article, the principles of language taxonomies construction depending on the social and political categorization of language space are introduced. It is proposed to strictly differentiate the concepts of language categorization and classification/typology/taxonomy. Categorization is understood as a form of cognition, it connects the subject and the object of cognition, therefore its products are representations of different levels of abstraction in the individual or collective consciousness. Taxonomies and classifications, as methods of cognition, refer to epistemology and represent principles of regulation by the result of categorization. Since the socio-political categorization of language space is fundamentally discursive in nature, therefore, it represents the points of view of various subjects of cognition, it is unlikely to talk about the existence of terminology in this field in the strict sense. We are dealing with multiple nominations stemming from different periods, ideologies and the pragmatic goals of various actors of glottopolitics, which leads to broad contextual synonymy and antonymy of nominations in this area. The discursive nature of these nominations results in a fundamental difference in the semantic field of formally similar nominations in different cultural and political regions, which complicates adequate translation and requires careful semantic research.